An outbreak no longer: factors contributing to the return of syphilis in Greater Manchester. Issue 4 (5th August 2003) - Ashton, M; Sopwith, W; Clark, P; McKelvey, D; Lighton, L; Mandal, D
Abstract : Background: In the past few years, increased diagnoses of syphilis have been reported in cities around Britain and Europe. Enhanced surveillance of cases began in 1999 to identify the epidemiology of this increase in Greater Manchester. Methods: Information was collected on all cases of syphilis newly diagnosed in genitourinary medicine (GUM) clinics in Greater Manchester between January 1999 and November 2002. The data collected included demographic information and information about other sexually transmitted infections, sexual behaviour, perception of risk of infection, and awareness of syphilis transmission. Results: The majority of cases identified were white homosexual men resident in Greater Manchester. Of the 414 cases diagnosed, 74% had either a primary or secondary stage of syphilis infection and 37% of cases were HIV positive. High numbers of individuals practised unprotected oral sex despite good awareness of the risk of infection with syphilis. There is evidence that the way people are meeting sexual contacts is changing, with increasing numbers meeting most of their partners through the internet. Conclusions: These findings have implications for targeting interventions. The provision of rapid diagnostic and treatment services is likely to be key for the control of syphilis and potentially of subsequent increases in HIV in the region.